Digital Bureaucracy: Challenges in Implementing the Electronic-Based Government System (SPBE) in the 3T Region of Sabu Raijua Regency - Rihi, David Wilfrid; Wadu, Jacob; Seran, Delila Angelina Nahak; Benyamin, Rouwland Alberto (JURNAL TRIAS POLITIKA, 2025)
This study examines the challenges of implementing the Electronic-Based Government System (SPBE) in Sabu Raijua Regency, one of Indonesia’s frontier, outermost, and least developed (3T) regions located in East Nusa Tenggara Province. The selection of Sabu Raijua as the focus of analysis is grounded in its representative status as a 3T area, which faces structural and contextual constraints in advancing digital governance. Employing a qualitative approach, the research involved in-depth interviews, field observations, and document analysis with 33 informants, including heads of local agencies, staff, and citizens as service recipients. The findings reveal four significant challenges in implementing SPBE for realizing digital bureaucracy in Sabu Raijua: (1) policy-related barriers, (2) institutional limitations, (3) inadequate infrastructure, and (4) weaknesses in application systems. SPBE enhances bureaucratic innovation and digital governance, thereby improving efficiency, accountability, and public participation. However, the implementation of SPBE in this region encounters unique challenges that demand innovative and adaptive approaches to ensure effectiveness and inclusiveness. Accordingly, the study highlights the need for locally tailored policies, adaptive and collaborative digital architecture, bottom-up approaches, and strengthening local bureaucratic capacity.